1987
DOI: 10.1111/j.1365-2265.1987.tb01145.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Glucocorticoids on Corticosteroid Binding Globulin

Abstract: To evaluate the effect of glucocorticoids on corticosteroid binding globulin (CBG), we measured the binding capacity and binding affinity of cortisol for CBG in normal subjects, patients receiving glucocorticoids and patients with Cushing's syndrome. Normal subjects had a mean binding capacity of 3.8 (+/- SD 0.7) X 10(-7) mol/l and mean binding affinity of 1.96 +/- 0.48 X 10(-8) M. Patients with Cushing's syndrome had a 40% decrease in binding capacity (2.3 +/- 0.4 X 10(-7) mol/l) compared to control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…In rats treated with dexamethasone. a decrease in serum CBG was observed and it was related to diminished CBG mRNA synthesis [23], whereas in adrenalectomized ani mals, CBG production was increased from perfused rat liver [21], These observations suggest that glucocorticoids may modulate CBG production and are consistent with the findings of decreased plasma CBG in Cushing syn drome [24] and in patients receiving glucocorticoids [25], A report on women with polycystic ovary syndrome found a significant reduction in immunoreactivc CBG and the authors speculated that it could be related to increased activity of the adrenal axis [26], Lack of diurnal variations in CBG however does not support the hypothe sis of a regulation of CBG production by glucocorticoids under physiological circumstances.…”
Section: Effects O F Glucocorticoidssupporting
confidence: 79%
“…In rats treated with dexamethasone. a decrease in serum CBG was observed and it was related to diminished CBG mRNA synthesis [23], whereas in adrenalectomized ani mals, CBG production was increased from perfused rat liver [21], These observations suggest that glucocorticoids may modulate CBG production and are consistent with the findings of decreased plasma CBG in Cushing syn drome [24] and in patients receiving glucocorticoids [25], A report on women with polycystic ovary syndrome found a significant reduction in immunoreactivc CBG and the authors speculated that it could be related to increased activity of the adrenal axis [26], Lack of diurnal variations in CBG however does not support the hypothe sis of a regulation of CBG production by glucocorticoids under physiological circumstances.…”
Section: Effects O F Glucocorticoidssupporting
confidence: 79%
“…2) and after the women were split by group (data not shown). We examined the correlation between the two parameters after splitting cortisol values by concentration ranges, excluding from the analysis the post-dexamethasone cortisol values, because of the in¯uence of exogenous glucocorticoids on circulating corticosteroid-binding globulin (CBG) concentrations (25). We found that the correlation was lost for plasma cortisol concentrations greater than 500 nmol/l (Fig.…”
Section: Correlations Between Plasma Salivary and Urinary Cortisolmentioning
confidence: 99%
“…108 The production of cortisol in adrenocortical cells in response to ACTH occurs within minutes, and there is a shift towards an increase in glucocorticoid and away from mineralocorticoid and androgen production. 113 The CBG concentration in serum and the CBG binding affinity are both decreased 22,23,26,238 resulting in a dramatic increase in the biological active free cortisol concentration. In addition, the glucocorticoid receptor shows an increased affinity to free hormone during the acute phase of critical illness.…”
Section: Hpa (Dys)function In Human Sepsismentioning
confidence: 99%